Komitmen atas SDGs-9, Tingkat Inovasi, dan Dampaknya Pada Kinerja Keberlanjutan Perusahaan - Ahmad Hambali (Universitas Kristen Krida Wacana, 2024)
This study aims to examine the influence of corporate commitment to SDGs 9 and innovation levels on the sustainability performance of companies listed on the Indonesia Stock Exchange. The research method used is panel data regression analysis with a sample of 203 companies over the period of 2016-2022. Sustainability performance and innovation level data were obtained from the Thomson Reuters database, while commitment to SDGs 9 was measured through content analysis of corporate sustainability reports. The results show that commitment to SDGs 9 and innovation levels have a positive and significant impact on corporate sustainability performance. These findings are consistent with institutional theory, which emphasizes the importance of external pressure in driving companies to adopt sustainable practices. This study contributes to the sustainability literature by affirming the crucial role of SDGs 9 and innovation in enhancing corporate ESG performance. The results also provide practical insights for companies and policymakers in designing effective sustainability strategies. Keywords: ESG, Innovation, Sustainability, Sustainable Development Goals (SDGs), SDGs 9